Understanding User’s Knowledge-Driven Competence to Identify Cloned and Authentic Facebook Pages of Newspapers - Ibrahim, Abubakar Tijjani; Ibrahim , Adamkolo Muhammed (PT Agung Media Publisher, 2025)
Cloned Facebook pages that mimic established newspapers pose a risk of misinformation, particularly for postgraduate students in Nigeria who are expected to have strong media-literacy skills. This study investigates their ability to distinguish authentic from cloned Facebook pages of Daily Trust and Vanguard, and identifies the cues and strategies they use in the evaluation process. Using a sequential explanatory mixed-methods approach, the study began with a survey of 372 postgraduate students across three universities in North-West Nigeria. It measured their knowledge of authenticity indicators such as verification badges, URLs, and contact details. This was followed by ten in-depth interviews with selected students and newspaper editors to explore their reasoning and institutional practices. Results show that fewer than 14% of students were aware of missing verification badges on cloned pages, and only about 20% recognized misuse of logos or names. Most relied on visual elements like logos and page titles rather than systematic checks. Editors also confirmed that clone detection is reactive, triggered mostly by user complaints. The findings indicate a gap between assumed competence and actual verification skills. The study recommends introducing a structured Digital Verification Training (DVT) program that includes theoretical instruction, hands-on exercises, case studies, and collaboration with media platforms to improve users' ability to verify online news sources.